COVID-19 Impact Monitoring : Malawi, Round 4 - Malawi National Statistical Office; World Bank (World Bank, Washington, DC, 2020)
In May 2020, the National Statistical Office (NSO), with support from the World Bank, has launched the High-Frequency Phone Survey on COVID-19, which tracks the socio-economic impacts of the pandemic on a monthly basis for a period of 12 months. The survey aimed to recontact the entire sample of households that had been interviewed during the Integrated Household Panel Survey (IHPS) 2019 round and that had a phone number for at least one household member or a reference individual. This report presents the findings from the fourth round of the survey that was conducted during the period of September 14 - September 29, 2020.